1989
DOI: 10.1002/ajmg.1320330228
|View full text |Cite
|
Sign up to set email alerts
|

IVIC syndrome: Report of a third family

Abstract: After the report of a second family with IVIC syndrome [Arias et al., 19801 by Sammito et al. [1988], we are presenting here a third family, with affected mother and son (Fig. 1).The X-ray examination of the affected mother (born in 1962) on the right, showed absence of thumb, first metacarpus, and 0s multangulum maius; a synostosis between the 0 s multangulum minus and 0 s capitatum; elongation of the 0s lunatum in a navicular-like shape; exostoses in proximal and middle phalanges of the index finger; short r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Oculo‐otoradial (OOR) and WT syndromes are autosomal dominant disorders that show phenotypic overlap with the present cases in that OOR and WT syndromes are characterized by skeletal anomalies involving the upper extremity, and are associated with mild to moderate thrombocytopenia (Gonzalez et al , 1977; Arias et al , 1980; Czeizel et al , 1989). Additional congenital malformations reported with OORS include radial ray hypoplasia, absent thumbs, impaired hearing, imperforate anus, strabismus and external ophthalmoplegia.…”
Section: Discussionmentioning
confidence: 77%
“…Oculo‐otoradial (OOR) and WT syndromes are autosomal dominant disorders that show phenotypic overlap with the present cases in that OOR and WT syndromes are characterized by skeletal anomalies involving the upper extremity, and are associated with mild to moderate thrombocytopenia (Gonzalez et al , 1977; Arias et al , 1980; Czeizel et al , 1989). Additional congenital malformations reported with OORS include radial ray hypoplasia, absent thumbs, impaired hearing, imperforate anus, strabismus and external ophthalmoplegia.…”
Section: Discussionmentioning
confidence: 77%
“…A second report of an Italian family occurred in 1988 [Sammito et al, 1988]; and in 1989 a third family from Budapest was also reported [Czeizel et al, 1989]. Phenotypically discordant Turkish monozygotic twin girls were later described [Elçioglu and Berry, 1997].…”
Section: Introductionmentioning
confidence: 96%
“…A second report of an Italian family occurred in 1988 [Sammito et al, 1988]; and in 1989 a third family from Budapest was also reported [Czeizel et al, 1989]. Phenotypically discordant Turkish monozygotic twin girls were later described [Elçioglu and Berry, 1997].…”
Section: Introductionmentioning
confidence: 99%